Religious Pluralism In The View Of Islam (Comparative Interpretation Of Sayyid Quthb And Maulana Farid Esack) - Karim, Dudung Abdul; Sekardilla, Tasya; Oki, Alber; Mahdor, Muslich Marzuki; Soleh, Rahmat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2024)
This research examines the different points of interpretation of religious pluralism to obtain coherent results on whether the pluralism referred to in the Qur'an is in the form of equality of every religion or plurality that respects each other with existing differences. The discourse with these two views creates bias in the interpretation of religious pluralism which has an impact on obscuring the concrete nature of the Qur'an. The type of research used is qualitative-descriptive-analytical research by explaining the explanation or depiction with clear and detailed words systematically, factually, and accurately based on existing data from library research. Furthermore, it is reduced by Abdul Hayy Al-Farmawi's muqarran method. The results of this study found that Sayyid Qutb disagrees with religious pluralism because religious plurality is a necessity, but not with religious pluralism. Maulana Farid Esack argues that whatever religion a person believes in as long as he believes in Allah and the last day and does righteous deeds, then he will get a guarantee of salvation.